2008
DOI: 10.3201/eid1406.071168
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone-ResistantSalmonella entericaSerotype Newport, France

Abstract: The multidrug-resistant (MDR) Salmonella enterica serotype Newport strain that produces CMY-2 β-lactamase (Newport MDR-AmpC) was the source of sporadic cases and outbreaks in humans in France during 2000–2005. Because this strain was not detected in food animals, it was most likely introduced into France through imported food products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 15 publications
3
38
0
4
Order By: Relevance
“…Further selection for a lineage containing this plasmid may reflect the common prophylactic use of tetracycline, because tetracycline resistance is also encoded on the same plasmid. It has been suggested that all MDR-AmpC strains have a recent global origin (2,25,39), and our assignment of all MDR-AmpC S. Newport isolates to two closely related STs within Newport-II is consistent with the recent clonal expansion from a single S. Newport strain. pSN254 is not conjugative, unlike other IncA/C plasmids (34), which might explain why the MDR-AmpC phenotype has apparently not spread to other STs of S. Newport.…”
Section: Ssupporting
confidence: 70%
See 1 more Smart Citation
“…Further selection for a lineage containing this plasmid may reflect the common prophylactic use of tetracycline, because tetracycline resistance is also encoded on the same plasmid. It has been suggested that all MDR-AmpC strains have a recent global origin (2,25,39), and our assignment of all MDR-AmpC S. Newport isolates to two closely related STs within Newport-II is consistent with the recent clonal expansion from a single S. Newport strain. pSN254 is not conjugative, unlike other IncA/C plasmids (34), which might explain why the MDR-AmpC phenotype has apparently not spread to other STs of S. Newport.…”
Section: Ssupporting
confidence: 70%
“…Salmonella enterica subspecies enterica (referred to herein as S. enterica) has been subdivided serologically into Ͼ1,500 serovars (35), but we focus on S. enterica serovar Newport (S. Newport) here because over the last decade it has been a very common cause of human salmonellosis in both the United States and Europe (13,16,27). Furthermore, multidrug-resistant S. Newport isolates that are also resistant to extended-spectrum cephalosporins (MDR-AmpC) have now been reported from several countries (3,24,36) and are a serious problem among both food animals and humans (17,25,36,48,67). MDR-AmpC isolates are resistant to ␤-lactams, including third-generation cephalosporins, aminoglycosides, tetracyclines, sulfonamides and chloramphenicol (12,36).…”
mentioning
confidence: 99%
“…The bla CMY-2 genes have also been detected in E. coli and Salmonella isolates from ground meat (54). The presence of bla CMY-2 plasmid-bearing Salmonella enterica serovars Newport and Typhimurium presumptively of animal origin has been reported in human clinical cases (17,18).…”
mentioning
confidence: 83%
“…140-to 160-kb) IncA/C plasmids (bla CMY-2 plasmids) from a diverse range of bacterial hosts, including Escherichia, Salmonella, Shigella, Klebsiella, Edwardsiella, and Aeromonas (31,35,50). These bla CMY-2 plasmid-bearing bacteria have been detected in mammals and fish without a documented or consistent pattern of antibiotic selection pressure (2,17,26,31,37,(50)(51)(52). There is a high prevalence (up to 100%) of bla CMY-2 plasmids reported in commensal and pathogenic bacteria such as Escherichia coli and Salmonella enterica in cattle herds across the United States (1,15,30,42,51).…”
mentioning
confidence: 99%
“…There have been several reports of IncA/C plasmids from various Salmonella and E. coli strains that harbor the bla CMY-2 gene and more recent reports of IncA/C plasmids harboring both bla CMY-2 and floR in human clinical isolates of Salmonella serovar Newport (7,14) and in an isolate of the fish pathogen Aeromonas salmonicida subsp. salmonicida from Atlantic salmon in Canada (10).…”
mentioning
confidence: 99%